2019
DOI: 10.1016/j.envpol.2019.04.120
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine concentrations in aquatic organisms from different trophic levels of the Sundarbans mangrove ecosystem and their implications for human consumption

Abstract: The Sundarbans, a highly biodiverse tropical ecosystem stretching across India and Bangladesh, is also the largest mangrove forest in the world. Organochlorine compounds (OCs) have been extensively used for agriculture and sanitary purposes in the region. OCs can accumulate in biological tissues and biomagnify in organisms through food webs, for which reason they reach high concentrations in top predators. Because marine food webs are long and marine predators are extensively used in the region as human food, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
4
1
Order By: Relevance
“…This indicates that DDT is still detected in commercial samples, reflecting the need for active monitoring programs in market samples. DDT levels quantified here were also higher than from crustaceans collected in other Asian countries (20-fold higher than in Bangladesh or Singapore (Bayen et al 2005;Borrell et al 2019), or even 40-fold higher than in Taiwan (Das et al 2020).…”
Section: Occurrence Of Insecticides On Seafoodcontrasting
confidence: 49%
“…This indicates that DDT is still detected in commercial samples, reflecting the need for active monitoring programs in market samples. DDT levels quantified here were also higher than from crustaceans collected in other Asian countries (20-fold higher than in Bangladesh or Singapore (Bayen et al 2005;Borrell et al 2019), or even 40-fold higher than in Taiwan (Das et al 2020).…”
Section: Occurrence Of Insecticides On Seafoodcontrasting
confidence: 49%
“…The use of the organochlorine DDT^( 135) was banned in the early 1980s in Bangladesh, but its production in the country continued until 1991, mainly for malaria control (Bergkvist et al, 2012). However, the use of DDT^( 135) in agriculture has increased since 2000 (Bergkvist et al, 2012;Borrell, Tornero, Bhattacharjee, & Aguilar, 2019). The World Bank reported that, of 161 pesticide formulations used in the country, 19% were extremely hazardous (WHO class I), 51% very hazardous (WHO class II), 10% moderately hazardous (WHO class III), and 20% were low risk (class U) (Dasgupta et al, 2005).…”
Section: Occupational Exposure To Pesticidesmentioning
confidence: 99%
“…Consequently, residues of pesticides are found "in an alarming proportion on vegetable crops" (Miah et al, 2014). For example, several studies have found pesticide residues in different vegetable samples such as tomatoes, okra, eggplant, long yard bean, cauliflower, as well as meat, milk, and fish (Bergkvist et al, 2012;Borrell et al, 2019;Hasan et al, 2019;Islam et al, 2018;Miah et al, 2014).…”
Section: Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…However, consumers are often concerned about hazardous chemical contaminants potentially present in fish and seafood. Indeed, the occurrence of lipophilic contaminants, such as nonpolar pesticides and polychlorinated biphenyls (PCBs), has been previously documented in various fish and seafood samples. , Additionally, various drugs are used in aquaculture production to control diseases and prevent mortality that can also accumulate in fish tissues to potentially cause harm to consumers.…”
Section: Introductionmentioning
confidence: 99%